Enhancing access to genetic resources for climate change adaptation in Kenya, Uganda and Tanzania: Seed catalogues of best perfoming varieties of sorghum in Dodoma and Singida Tanzania - Otieno, Gloria Atieno; Recha, Tobias; Fadda, Carlo; Halewood, Michael; Mollel, Margaret; Bundala, Zakao; Kazungu, Jonathan Sikitu (Bioversity International, 2020)
Climate change poses an increasing threat to food and nutrition security of resource-poor farmers globally. In Tanzania, homogenization of agriculture to single crops or varieties coupled with the associated loss of biodiversity has further decreased the resilience of resource-poor farmers. The loss of genetic diversity in farmers’ custody has greatly narrowed the gene pool from which they depend on. In order to help them adapt to climate change, the project “Promoting Open Source Seed Systems for Beans, Millet and Sorghum for Climate Change Adaptation” funded by the Benefit-sharing Fund (BSF) of the International Treaty on Plant Genetic Resources for Food and Agriculture (ITPGRFA) was implemented in Kenya, Uganda and Tanzania. Through this project, farmers in Dodoma and Singida in Tanzania tested and evaluated the performance of 24 varieties of sorghum for drought tolerance, yield, early maturity, pest and diseases and taste and selected 10 best performing. This catalogue presents these top selected varieties including their agronomic attributes and nutritional benefits.